2021
DOI: 10.1007/s13273-021-00178-x
|View full text |Cite
|
Sign up to set email alerts
|

Glycosidic flavonoids and their potential applications in cancer research: a review

Abstract: Purpose of review Every year, the cancer patient registry increases, and the leading cause of death in a global context. Plant-based molecules are gaining attention in cancer research due to the side effects of chemotherapy. A glycosidic derivative of flavonoid (GDF) plays a significant role in cancer proliferation mechanisms. GDF inhibits cell proliferation by elevating the expression of apoptotic proteins, altering the expression of nuclear factor-kappa B (NF- κB), and decreasing mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Prunetionoside, a flavonoid compound, has potent cytotoxic effects and can cause necroptosis in AGS gastric cancer cells. Similarly, scutellarein, another flavonol, initiates an extrinsic pathway of apoptosis in HepG2 liver cancer cells and decreases the expression of cyclin protein [ 28 ]. In the optimization of therapy and in the search for new anticancer agents, the biological potential, bioavailability, cost-effectiveness, and minimal side effects of flavonoids make them promising cytotoxic anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
“…Prunetionoside, a flavonoid compound, has potent cytotoxic effects and can cause necroptosis in AGS gastric cancer cells. Similarly, scutellarein, another flavonol, initiates an extrinsic pathway of apoptosis in HepG2 liver cancer cells and decreases the expression of cyclin protein [ 28 ]. In the optimization of therapy and in the search for new anticancer agents, the biological potential, bioavailability, cost-effectiveness, and minimal side effects of flavonoids make them promising cytotoxic anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
“…Ramos et al (2010), found the flavonoid orientin in an ethanolic leaf extract of Passiflora tripartita. This flavonoid was studied by Abusaliya et al (2022), and found that it has an application in the treatment against cancer. The administration of orientin-containing nanoparticles in mice was reported to provide antidepressive activity in mice (Alves et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, since flavonoid compounds can reduce the DNA damage caused by cisplatin, whether they affect the ability of cisplatin to kill cancer cells still needs further investigation. A literature review presented that the flavonoids in many plant extracts can promote the apoptosis of gastric cancer cell lines (Lee et al, 2012;Bhosale et al, 2021;Abusaliya et al, 2022). These studies demonstrated that flavonoids can stall the progression of the G2→M cell cycle in AGS gastric cancer cell lines and then cause apoptosis.…”
Section: Discussionmentioning
confidence: 99%